PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NHT UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMPI AL-HASANAH PANDAU JAYA - Apriadi Apriadi; Zuhri Zuhri; Armis Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis study aims to improve student learning outcomes in teaching and learning in SMPI Al-Hasanah Pandau Jaya to implement cooperative learning model numbered heads together in math. This study uses classroom research. This is done in two cycles. Activities and student learning outcomes data were obtained by collecting activity data using observation sheets and daily test. Data collected were analyzed statistically werescore descriptive. The results in cycle I. found that the percentage of students who achieve the KKM is 63.15% and the award is based on the first cycle of the four teams are given 3 great team and one team is given a super, while in the second cycle of the 4 teams are given a great team. The conclusian research shows that the application of cooperative learning model to jointly head numbered approach can improve students' mathematics learning outcomes..Key words: numbered heads together, learning outcomes